Lighting efficiency and effects on human activities in library at Universiti Teknologi Petronas / Nur Hazirah Othman and Izzat Anuar - Othman, Nur Hazirah; Anuar, Izzat (2018)
The aim of this study is to show that proper lighting is crucial for the users to improve their performance and quality of time spent in library. Good lighting design in library buildings is the result of both technical skill and art on the part of the designer. The following study discusses the most important issues in daylighting design for modern libraries. It is not an instruction manual on how to light a library, but it sets specific criteria that, if met, will avoid major mistakes. These criteria also can be used as a checklist for assessing the lighting in an existing library to see if improvements are needed. The quality of lighting really gives a big impact to human behavior and this study of the lighting will give additional proof that human behavior is actually affected by the lighting in the library. In conclusion, the more appropriate the lighting, the more effective will the activities in the library be.